Prinsip, implementasi, dan tantangan dalam sistem ekonomi syariah modern - Nafila, Yusratun - (Maliki Interdisciplinary Journal, 2025)
Sharia economic law is a branch of Islamic law that regulates economic activities based on Sharia principles. This study aims to understand the fundamental concepts of Sharia economic law, its implementation in the financial and business sectors, and the challenges faced in its application. The findings indicate that Sharia economic law prohibits practices such as riba, gharar, and maysir while emphasizing risk-sharing principles through contracts like mudharabah and musyarakah. The implementation of Sharia economics has expanded in banking, capital markets, and trade sectors. However, challenges persist, including limited public understanding, suboptimal regulations, and competition with conventional economic systems. Therefore, broader education and stronger policy support are necessary to ensure the sustainable growth of Sharia economics in the future.